HUBUNGAN PENGETAHUAN KESEHATAN GIGI DAN MULUT TERHADAP JUMLAH KARIES ANAK KELAS III - V DI SD MUHAMMADIYAH SANGONAN II GODEAN YOGYAKARTA - Almujadi Almujadi; Taadi Taadi (Jurnal Kesehatan Gigi, 2017)
TITLEThe relationship of dental health knowledge and dental caries prevalence in 3rd to 5th level of school children in SD Muhammadiyah Sangonan II Godean YogyakartaABSTRACTKnowledge play an important part to build oral and dental hygiene behaviour in children. Dental caries is one of the hard tissue disease caused by bacterial activity that will make dental hard tissue soften and cavity will appear. The purpose of this research was to find the relation between oral and dental health knowledge and dental caries cases among pupils grade III-IV SD Muhammadiyah Sangonan II, Godean.It was an analytical survey research, with cross sectional sampling. The independent variable was knowledge about oral and dental health, and the dependent variable was total caries number among pupils grade III-IV. It used total population sampling, all of the pupils in grade III-IV, with total 60 children, as the subjects. Questionnaire and direct examination used for the data collection. The data analysis for hypothesis testing used Spearman rank.Most of the children have good knowledge about oral and dental health, 49 childs (81,7%) could answer correctly 15-20 questions. On the other hand, most of the children (34 childs or 56,7%) have ≥3 caries or in category ‘many caries numbers’. There was no corellation between oral and dental health knowledge and total caries number among pupils grade III – V SD Muhammadiyah Sangonan II Godean, with significancy 0,408 (sig≥0.05).